PENGATURAN PIDANA DENDA DALAM PENCAPAIAN KEADILAN BAGI ANAK YANG MENJADI KORBAN TINDAK PIDANA PENCABULAN - Indah Permata Sukma; Erdianto Effendi; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
One criminal sanctions in felony obscenity against children is a criminal sanction fines. criminal fines imposed and then pulled by the Prosecutor General and submitted to the state. In this case the fine is not good for the victim because the victim did not get anything out of that has been levied by the state. In this case the penalty is only useful for the country but not beneficial to the offender and the victim. Based on the Law of the Republic of Indonesia Number 31 of 2014 on the Amendment of Act No. 13 of 2006 on the Protection of Witnesses and Victims in section 7A and 7B stated that crime victims can get restitution and compensation,This type of research will author is a normative legal research (legal research) or also called the research literature, the research done with normative juridical approach under study is library materials or secondary data, which consists of primary legal materials, secondary law, and tertiary legal materials. The type of research that I use is the study of the principles of law.The results of research by the author is the first, setting the penalty contained in Law No. 35 of 2014 concerning amendments to the Law No. 23 of 2002 on the protection of children. Secondly, i Ideally the setting criminal penalties for children who are victims of felony obscenity would be better that they directly or good for the child victims to remember children who are the future generation the ideals of the nation that destroyed his future by perpetrators of abuse.Keywords: child abuse, criminal fines, Justice